Analisis Framing Tentang Wacana Terorisme di Media Massa (Majalah Sabili) - Ummy Hanifah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2019)
Mass media has an important role in delivering information and entertainment to their publics. Media is not fully being neutral. Mass media represent certain interest whether economy, politic, culture, ideology nor religion. By using the theory content’s media from Shoemaker and Reese, there are many factors that influence the media’s content: the journalist, ideology, routine, owner, etc. According to theory making news production, news is not selectet but it is formed. The journalist made the event which one has news value and not. Sabili is the object of this study. This article wants to examine how media (Sabili) contructed terrorism issue to its public. Framing analysis is a technic to know how media (Sabili) contructed terrorism. And also framing can show the readers media bias. Researcher used qualitative method and framing analysis from Robert N Entman for the text. The framing analysis framework consisting of definig problems, cause’s diagnosis, make judgement’s moral and treatment recommendation. The result of this study addressed that Sabili was constructed the the police as actor and moslems activist as victim. And from the text Sabili supported to moslems activist and there is media bias. And also there is partisanship from Sabili to moslem activist. Media massa memiliki peran penting dalam menyampaikan informasi dan hiburan kepada public. Media tidak sepenuhnya bersikap netral. Media massa mewakili kepentingan tertentu entah itu ekonomi, ideologi, budaya bahkan agama. Dengan menggunakan teori dari Shoemaker dan Reese, terdapat banyak factor yang mempengaruhi isi media diantaranya ialah jurnalis, ideologi, rutinitas, pemilik dan lain-lain. Menurut pandangan pembentukan berita, berita merupakan hasil pembentukan bukan pemilihan. Wartawan yang menentukan suatu peristiwa memiliki nilai berita atau tidak. Dalam penelitian ini Sabili ialah obyek dalam penelitian. Artikel ini berupaya melihat bagaimana media dalam hal ini Sabili mengkonstruksikan terorisme dan juga pembingkaian dapat menunjukkan kepada pembaca bias media. Peneliti menggunakan metode kualitatif dengan menggunakan analisis framing dari Robert N. Entman untuk menguji teks. Kerangka analisis framing yang terdiri dari defining problems, cause diagnosis, make is judgement’s moral and treatment recommendation. Hasil dari studi ini menunjukkan bagaimana Sabili mengkonstruksikan Polisi sebagai actor (pelaku) dan kaum aktivis muslim sebagai korban. Selain itu juga ada keberpihakan Sabili dalam pemberitaan yang disampaikan.